Nucleotide sequence of the 5' noncoding region and part of the gag gene of mouse mammary tumor virus; identification of the 5' splicing site for subgenomic mRNAs. - Fasel, N (1983)
We have determined the sequence of the first 1371 nucleotides at the 5' end of the genome of mouse mammary tumor virus using molecularly cloned proviral DNA of the GR virus strain. The most likely initiation codon used for the gag gene of mouse mammary tumor virus is the first one, located 312 nucleotides from the 5' end of the viral RNA. The 5' splicing site for the subgenomic mRNA's is located approximately 288 nucleotides downstream from the 5' end of the viral RNA. From the DNA sequence the amino acid sequence of the N-terminal half of the gag precursor protein, including p10 and p21, was deduced (353 amino acids).